URGENSI SINGLE BASIC MAP UNTUK PERLINDUNGAN SUMBER DAYA AIR DALAM PENATAAN RUANG - Sardjana Orba Manullang Manullang; Yessy Kusumadewi Kusumadewi; Verawati Br Tompul Tompul; Iis Isnaeni Nurwanty Nurwanty (Universitas Majalengka, 2022)
Abstract Water Resources is one of the natural resources that must be preserved. Water Resources is one part of the category of the environment that can not be renewed. Conflicts related to water resources happen a lot, especially that related to the overlap of licensing. The research method in this paper uses the Normative Juridical research method, where the study focused on the rules – rules relating to spatial planning. Assessment of study that assessed based on history, giving hints how a lot of conflicts over water resources. To overcome this, it is necessary the existence a policy referred to as the basic single map in the arrangement of the space.